Satyagraha: The Gandhian Way. Issue 2 (December 2016) - Jahanbegloo, Ramin
This article highlights the key concepts of Gandhi's philosophy of Satyagraha and its intellectual origins by drawing extensively on his formulations of the right to civil disobedience and non-cooperation with unjust laws. This is followed by a detailed examination of the relevance of Gandhi's idea of Satyagraha. The author concludes that Gandhi's practice of Satyagraha provides us with a desperately needed alternative in the 21st century.